Republic of St. Peter : the Birth of The Papal State, 680-825. (Middle Ages Ser., 1986)
The Republic of St. Peter seeks to reclaim for central Italy an important part of its own history. Noble's thesis is at once original and controversial: that the Republic, an independent political entity, was in existence by the 730s and was not a creation of the Franks in the 750s. Noble examines the political, economic, and religious problems that impelled the central Italians-and a succession of resolute popes-to seek emancipation from the Byzantine Empire. He delineates the social structures and historical traditions that produced a distinctive political society, describes the complete governmental apparatus of the Republic, and provides a comprehensive assessment of the Franco-papal alliance.